Human Rights and the Fourth Industrial Revolution in South Africa (Adams et al) - Nyamadzawo Sibanda (Digital Policy Studies)
In this seven-chapter report, the authors present a guide to the policy development of human rights-based fourth industrial revolution (4IR) policies in South Africa. Based on the input given during a workshop organized by the South African Human Rights Commission (SAHRC), at the beginning of March 2020, the comprehensive report covers various areas in which artificial intelligence (AI) and 4IR technologies are employed, or to be employed, in South Africa. The authors lay a foundation for the discussion within the current social-economic and political development landscape of South Africa, through their engagement with the various development policy trajectories as they conceptualize technological transformation. In the same breath, the report acknowledges that any successfully implemented 4IR policy regime would have to acknowledge and engage sources and dynamics of current socio-economic challenges in the country, such as unemployment, poverty, and inequality (p. 1; p. 93). The argument put forward in this regard is that while the anticipated technological transformation is meant to help various facets of South African life (p. 8-12), ignoring the extant challenges could hurt any chance of beneficial technological transformation (p.58). In Chapter 2, the report engages various aspects of data governance in South Africa through an analysis of various pieces of extant policy, with a comprehensive comparison to international (UNHRC) and regional (ACHPR) policy instruments. While the report acknowledges the nascency in the development is such policies, both internationally and within the country, it also notices various lacuna in the extant policies. Of concern are various implementation gaps in most sectoral (DSI, DCDT, DTIC) statutes in South Africa.